2021
DOI: 10.1002/pbc.29200
|View full text |Cite
|
Sign up to set email alerts
|

Late adverse effects of childhood acute lymphoblastic leukemia treatment on developing dentition

Abstract: Background: Childhood cancer survivors show a variety of late adverse effects on dental health. The purpose of this study was to examine the prevalence and severity of dental abnormalities in permanent dentition in childhood leukemia survivors.Materials and methods: Retrospective analysis of panoramic radiographs was performed for 178 childhood leukemia survivors aged below 17 years at the time of diagnosis. Sex, age at diagnosis, interval between ALL diagnosis and the follow-up radiograph, treatment protocol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Although these dental problems were not disabling and could be surgically corrected, they had potential impact on functional and aesthetic prognoses. Previous studies showed that the prevalence of root abnormalities ranged from 1.3 to 5.6%, and microdontia from 1 to 2% in a population of healthy children ( 11 ). The prevalence of hypodontia varies between 4 and 8% depending on the ethnic background ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these dental problems were not disabling and could be surgically corrected, they had potential impact on functional and aesthetic prognoses. Previous studies showed that the prevalence of root abnormalities ranged from 1.3 to 5.6%, and microdontia from 1 to 2% in a population of healthy children ( 11 ). The prevalence of hypodontia varies between 4 and 8% depending on the ethnic background ( 12 ).…”
Section: Discussionmentioning
confidence: 99%